Tissue engineering in urology - Matoka, Derek J.; Cheng, Earl Y. (Canadian Urological Association Journal, 2013)
Tissue engineering encompasses a multidisciplinary approach geared toward the development of biological substitutes designed to restore and maintain normal function in diseased or injured tissues. This article reviews the basic technology that is used to generate implantable tissue-engineered grafts in vitro that will exhibit characteristics in vivo consistent with the physiology and function of the equivalent healthy tissue. We also examine the current trends in tissue engineering designed to tailor scaffold construction, promote angiogenesis and identify an optimal seeded cell source. Finally, we describe several currently applied therapeutic modalities that use a tissue-engineered construct. While notable progress has clearly been demonstrated in this emerging field, these efforts have not yet translated into widespread clinical applicability. With continued development and innovation, there is optimism that the tremendous potential of this field will be realized. L’ingénierie tissulaire englobe une approche multidisciplinaire axée sur le développement de substituts biologiques en vue de rétablir et de maintenir la fonction normale de tissus lésés. L’article qui suit passe en revue la technologie fondamentale utilisée pour générer des greffons implantables produits par ingénierie in vitro et possédant des caractéristiques in vivo correspondant aux tissus sains équivalents sur les plans physiologique et fonctionnel. Nous examinons également les tendances actuelles en ingénierie tissulaire visant à adapter des échafaudages tissulaires, à promouvoir l’angiogenèse et à dégager une source optimale de cellules implantables. Enfin, nous décrivons plusieurs modalités thérapeutiques actuellement mises en application utilisant un échafaudage créé par ingénierie tissulaire. En dépit de progrès remarquables dans ce domaine en effervescence, les efforts déployés ne se sont pas encore traduits par une applicabilité clinique étendue. Des développements et des percées continus permettent d’être optimiste face au potentiel prodigieux de ce domaine.